Training Need of Fish Farmers in Bishnupur District of Manipur: An Analysis - B. Hijam , D. K. Pandey and H K De, (Indian Journal of Extension Education, 2015)
The present study was conducted in Bishnupur district of Manipur in order to ascertain the training need of fish farmers.The data was gathered using pre-tested structured interview schedule. Overall training need of the respondents was 58.71percent. Maximum training need of fish farmers was observed towards fish diseases control, hatchery management/fishseed production/nursery management and Aquaculture. Culture of commercially important fish species in aquaculture,preparation of shidal in fish processing, identification of different causing factor of fish diseases, maintenance and use ofportable plastic carp hatchery and design and construction of hatchery unit were identified as key areas for training need ofthe fish farmers. The study suggests that concerted training efforts on the part of Department of Fisheries and otherstakeholders is needed for realizing the potential of fish farming in Manipur.